Literature Review: The Effect of Non-Pharmacological Methods on Perineal Pain Intensity and Wound Healing in Women with Normal Postpartum Recovery - Aticeh Aticeh; Sri Mulyati; Endah Dian Marlina; Rosita Syarifah; Winancy Winancy (GLOBAL HEALTH SCIENCE GROUP, 2026)
Perineal pain following vaginal delivery is a prevalent issue that significantly impacts postpartum quality of life and surgical incision recovery. Non-pharmacological interventions, notably thermal therapies, offer a non-invasive alternative to medication. This systematic review evaluates the efficacy of non-pharmacological methods on perineal pain intensity and wound healing during normal postpartum recovery. A systematic search was performed across Google Scholar and NCBI PubMed for studies published between 2014 and 2025. Following PRISMA guidelines, 9 articles were selected for qualitative synthesis. Findings indicate that warm compresses facilitate vasodilation, enhancing blood circulation and tissue regeneration. Conversely, cold compresses effectively induce local analgesia, reducing inflammation, edema, and nerve sensitivity. Both methods significantly decrease pain scores and accelerate the REEDA (Redness, Edema, Ecchymosis, Discharge, and Approximation) healing scale. Non-pharmacological methods are safe, cost-effective, and evidence-based interventions that should be integrated into standard midwifery and nursing protocols to optimize maternal recovery.